Antemortem diagnosis with multiple random skin biopsies and transbronchial lung biopsy in a patient with intravascular large B-cell lymphoma, the so-called Asian variant lymphoma. (14th March 2014) - Nishizawa, Tomotaka; Saraya, Takeshi; Ishii, Haruyuki; Goto, Hajime
Abstract : A 59-year-old, previously healthy man presented to our hospital, with a 3-month history of high fever, nocturnal sweating and exertional dyspnoea. Aggressive diagnostic procedures such as multiple random skin biopsies and transbronchial lung biopsy (TBLB) led to an antemortem diagnosis of intravascular large B-cell lymphoma (IVLBCL), which showed abundant CD20 atypical lymphocytes aggregated in lumina of small vessels. The 29 cases diagnosed with IVLBCL during their lifetime by TBLB were reviewed. Their clinical features included respiratory symptoms (hypoxaemia, dyspnoea and dry cough) and persistent fever. IVLBCL patients show various radiological patterns (ground glass opacities, multiple centrilobular nodules, interlobular septal thickening, interstitial shadows and thickening of bronchovascular bundles), suggesting lymphatic or haematological spread. Antemortem diagnosis of IVLBCL is difficult, but a multidisciplinary approach, with aggressive multiple random skin biopsies and/or TBLB, should be considered in patients with respiratory symptoms that are refractory to antibiotics or prednisolone treatment.